K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 9 2016

Ta có :

\(\frac{x}{2^2}+\frac{x}{2^3}+\frac{x}{2^4}=\frac{x}{3^2}+\frac{x}{3^3}+\frac{x}{3^4}\)

\(\frac{x}{2^2}+\frac{x}{2^3}+\frac{x}{2^4}-\frac{x}{3^2}-\frac{x}{3^3}-\frac{x}{3^4}=0\)

\(x^2\left(\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}-\frac{1}{3^2}-\frac{1}{3^3}-\frac{1}{3^4}\right)=0\)

\(\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}-\frac{1}{3^2}-\frac{1}{3^3}-\frac{1}{3^4}\ne0\Rightarrow x^2=0\)

\(x=0\)

26 tháng 1 2016

kho....................wa..................troi.......................thi.....................ret.................lanh................wa..................tich............................ung.........................ho..............minh......................cho....................do....................lanh

1 tháng 10 2016

x = 0 đó bạn!

5 tháng 7 2016

x4+2x3y-2x3+x2y2-2x2y-x(x+y)+2x+3

= x4+2x3y-2x3+x2y2-2x2y-x2.xy+2x+3

= x4+x3y-2x3+x3y+x2y2-2x2y-x2-xy+2x+3

= x3.(x+y-2)+x2.(x+y-2)-x.(x+y-2)+3

= x3.0+x2.0-x.0+3

= 3